Pengaruh Partisipasi Anggota Terhadap Peningkatan Sisa Hasil Usaha (SHU) Pada Koperasi Simpan Pinjam (KSP) Credit Union Bahtera Sejahtera Maumere - Maria Vionsiana Blogon; Yosefina Andia Dekrita; Cicilia Ayu Wulandari Nuwa (Lembaga Pengembangan Kinerja Dosen, 2023)
The research background was the low residual business results in the saving and loan cooperative of Bahtera Sejahtera Maumere Credit Union. The aims of this study were (1) to find out the description of member participation and remaining results of operation in the Savings and Loan Cooperative of Bahtera Sejahtera Maumere Credit Union; (2) to determine the influence of member participation and Remaining Results of Operation in the Savings and Loan Cooperative of Bahtera Sejahtera Maumere Credit Union. The population in this study is financial report data at the Saving and Loan Cooperative of Bahtera Sejahtera Maumere Credit Union. The sample in this research were financial statements data from 2017-2021. The research method employed simple linear regression analysis using quantitative data. Hypothesis testing was done through the t-test. The results obtained indicated that member participation did not influence the remaining results of operation. this condition occurs due to do average member did not actively make deposits, particularly the 26% obligatory savings. Another factor was the large operating expenses at Savings and Loan Cooperative of Bahtera Sejahtera Maumere Credit Union as a cause of increasing in member participation that not significantly contributed to the acquisition remaining results of operation.